Surgical outcomes of strabismus after iatrogenic ophthalmic artery occlusion caused by cosmetic filler injections - Hee Kyung Yang (BMC Ophthalmology, 2019)
Abstract Background To investigate the surgical outcomes of strabismus related to iatrogenic occlusion of the ophthalmic artery and its branches from cosmetic facial filler injection. Methods A retrospective study was performed on 6 patients who underwent strabismus surgery among 23 patients who had suffered occlusion of the ophthalmic artery and its branches after cosmetic facial filler injection. Initial, preoperative and final ocular motility examinations, the type of surgery and surgical outcomes were evaluated. Results At initial presentation, visual acuity was no light perception in 5 patients and hand motion in one patient. Five out of 6 patients showed initial ophthalmoplegia. Among these 5 patients, eye motility fully recovered in 3 patients although sensory strabismus developed during follow-up, while the remaining 2 patients had persistent ocular motility limitations. Strabismus surgery was performed at 2.2 ± 1.5 years after iatrogenic ophthalmic artery occlusion. Preoperatively, 5 of the 6 patients showed exotropia, and one patient had esotropia. Vertical deviation was found in 3 out of 6 patients in addition to the horizontal deviation. Successful outcome was achieved only in the 4 patients without persistent ophthalmoplegia after 1.4 ± 1.0 years from surgery. The other two patients with persistent ocular motility limitations failed to achieve successful alignment after surgery, and one patient eventually underwent evisceration due to phthisis bulbi. Conclusions In our study, surgical outcomes of strabismus caused by cosmetic facial filler injection were successful only in patients without persistent ophthalmoplegia at the time of surgery.